The Rights of Nature and its Legal Personality A Conceptual Revolution - Khalaf, Husam (Journal of Legal Sciences, 2025)
Environmental damage and the worsening climate situation increasingly raise the question of measures to be taken to protect the environment. Among the possible legal tools, the concept of legal personhood (or personality) is mentioned, which guarantees the recognition of rights. Until now reserved for natural persons and groups of people, the concept could be expanded to non-human entities, including certain elements of nature, such as animals and rivers. A few concrete experiments support this movement, which is gaining momentum around the world, despite still significant resistance. Should we therefore grant legal personality to nature, or should humans remain the sole holders of rights?